Vaccination With Recombinant Adenoviruses Expressing the Bluetongue Virus Subunits VP7 and VP2 Provides Protection Against Heterologous Virus Challenge - Rojas, José Manuel; Barba-Moreno, Diego; Avia, Miguel; Sevilla, Noemí; Martín, Verónica (Frontiers in Veterinary Science, 2021)
Bluetongue virus (BTV) is the causative agent of a disease that affects domestic and wild ruminants and produces important economic losses. BTV is an arbovirus from the Reoviridae family that is typically transmitted by the bite of infected Culicoides midges. BTV possesses multiple serotypes (up to 28 have been described), and immunity to one serotype offers little cross-protection to other serotypes. The design of vaccines that provide protection across multiple serotypes is therefore highly desirable to control this disease. We previously reported that a recombinant replication-defective human adenovirus serotype 5 (Ad5) that expresses the VP7 inner core protein of BTV serotype 8 (Ad5VP7-8) induced T cell responses and provided protection. In the present work we evaluated as BTV vaccine the combination of Ad5VP7-8 with an Ad5 that expresses the outer core protein VP2 from BTV-1 (Ad5VP2-1). The combination of Ad5VP2-1 and Ad5VP7-8 protected against homologous BTV challenge (BTV-1 and BTV-8) and partially against heterologous BTV-4 in a murine model. Cross-reactive anti-BTV IgG were detected in immunized animals, but no significant titres of neutralizing antibodies were elicited. Ad5VP7-8 immunization induced T cell responses that recognized all three serotypes tested in this study, and primed cytotoxic T lymphocytes specific for VP7. This study further confirms that targeting antigenic determinant shared by several BTV serotypes using cellular immunity could help develop multiserotype BTV vaccines.